Evaluation of Drop Volume Consistency of Eyedrop Bottles for New Generic Prostaglandin Analogue, Latanost® in Glaucoma Treatment - Jessica S. C. Ng; Yi X. Tan; Nor A. A. Alwi; Kar M. Yee; Ahmad H. A. Rashid; Ka-Liong Tan; Chuei W. Leong (Dr. Yashwant Research Labs Pvt. Ltd, 2024)
Indexed by Scopus